The effect of income on net profit of banks before and during the Covid-19 pandemic - Anjelina Lamablawa; Eko Yuni Prihantono; Dimas Eka Pratama (Jurnal Penelitian, 2022)
During the Covid-19 pandemic, the banking sector experienced a decline in performance in terms of funding and lending. This downturn had significant implications on the income and net profit of banks, leading to operational challenges. This study aims to examine the effect of income on net profit before and during Covid-19 in State-Owned Banks (SOBs) in Indonesia. We included all existing SOBs in Indonesia, totaling 64 firms-quarterly observations during the period from 2018 to 2021. The research methodology involved regression analysis and a comparative study using Paired Sample Test. Our findings indicate that income has a significant impact on net profit. Furthermore, we demonstrate that there was no difference in bank income before and during the Covid-19 pandemic. However, there were variations in the net profit obtained by the banks. This phenomenon can be attributed to decreased interest margins as banks had to lower the interest rates on deposits without reducing the interest rates on loans.